A educação infantil em Goiás: percursos e contradições nas décadas de 1980 e 1990 - Costa, Maria Aparecida (2016)
This research, entitled The Early Childhood Education in Goiás in the 1980s and 1990s: pathways and contradictions linked to the line of research Training, Teacher Professionalization and Work Education of the Postgraduate Program in Education, of Faculty of Education, of Federal University of Goiás. Integrates design Public Policy and Education of Children in Goiás: history, concepts, projects and practices developed by the Center for Studies and Research of Childhood and its Education in Different Contexts (NEPIEC). The research adopted the perspective socio-historical dialectic, with the objective to know the history process of the institutions of children education who were under the responsibility of public power state in the 1980s and 1990s and to identify where they are today and designs educational they develop. As a methodological option, the survey was conducted in joint steps, covering literature, documentary research and empirical step, in which were used: questionnaires, interviews and site visits to four municipalities in Goiás (Anápolis, Goiânia, Senador Canedo and Trindade). The research was guided by the following questions: The State has structured public policies to ensure the provision of Early Childhood Education for children 0-6 years? State institutions existing Early Childhood Education in the 1980-1990 period are still functioning? As are today, that social purpose and which educational projects they propose? The theoretical dialogue throughout the research process took place with various scholars, such as: Almeida (2011), Alves (2014), Barbosa (1997, 1999a, 2000, 2001, 2003, 2006), Marx (2003), Moura (2002) Kuhlmann (2007), Priore (2008) and Sposito (1993). The research confirms previous studies that indicate the absence of documentary sources and highlights the need for childhood education institutions rebuild their files and thus preserve the history. Contradictions in Early Childhood Education was observed in the 1980s and 1990s, in which the data show that the state fails to comply with the legal requirements for establishing public policies for Early Childhood Education. In addition, also it found is that, in the studied time, there are educational projects that demonstrated the adoption of textbooks in early childhood education. There has been undeniable progress in legislation directed to children 0-6 years, however, are perceived influences of neo-liberalism in the laws and official documents and, consequently, professional identity building childhood education and continuing education.